Social Entrepreneurship: Promoting Sustainable Development of Micro Enterprises in Nepal - Rai, Dev Raj; Upadhyay, Pramod Raj; Pathak, Resham Raj (Journal of Productive Discourse, 2025)
This study examines the role of social entrepreneurship in advancing sustainable development in Nepal by focusing on the contributions of micro-enterprises to economic growth, environmental sustainability, and social inclusion. Employing a mixed-methods research design, the study integrates qualitative insights from semi-structured interviews with quantitative analysis of secondary data collected from 140 participants across the Kathmandu, Lalitpur, and Bhaktapur districts. Statistical tools—including chi-square tests, descriptive statistics, and correlation analyses—were utilized to assess the relationships among the variables. Findings reveal that micro-enterprises play a pivotal role in stimulating economic development by fostering job creation, skill development, and the empowerment of marginalized communities. Environmental sustainability initiatives, such as waste reduction and resource management, were found to have a significant positive impact on sustainable development. However, the relationship between social inclusion and social development was not statistically significant, indicating limited engagement with certain vulnerable groups. Additionally, while social entrepreneurship is positively associated with sustainable development, the strength of this relationship is weak, and a negative association was observed between economic growth and the role of social entrepreneurship in Nepal. These results highlight the need for more structured social inclusion programs and enhanced policy interventions to maximize the impact of social entrepreneurship in resource-limited environments. The study provides valuable insights for policymakers, practitioners, and researchers aiming to bolster sustainable development through targeted social entrepreneurship strategies in Nepal.